Comorbidity of disruptive behavior disorders and intermittent explosive disorder - Karam Radwan; Emil F. Coccaro (BMC, 2020)
Abstract Background Aggressive behavior in children and adolescents may be accounted for by several disruptive behavioral disorders (DBD) including attention-deficit/hyperactive (ADHD), conduct (CD), and oppositional defiant (ODD), disorders and intermittent explosive disorder (IED). The comorbidity among the DBDs is well known, but not its comorbidity with IED. Method We reanalyzed data from the National Comorbidity Studies (adolescents and adults), and from a large clinical research adult sample, to estimate the comorbidity of IED with each of the DBDs and to explore correlates of these comorbidities. Results The rate of current comorbidity between IED and the DBDs ranged from 10 to 19%, in adolescents (5-14% in adults) with odds ratios of about five. The onset of ADHD typically appeared before onset of IED while onset ODD and CD more typically appeared before that of IED in adolescents and about equally before or after IED in adults but IED persisted outside the duration window in many (ADHD) or most (ODD, CD) cases. Measures of impulsive aggression severity were highest in those with IED+DBD but relatively low in those with DBD alone while measures of DBD severity were highest in those with DBD alone and in those with IED+DBD. Conclusion Despite the comorbidity of IED with the DBDs, IED can be separated from the DBDs over time and in terms of severity measures of IED and of DBD. Overall, impulsive aggression varies with IED while DBD behaviors vary with DBD. Based on this, clinicians should consider IED in their differential in the workup of impulsively aggressive children and adolescents.